AI Triage vs. Emergency Room Triage: A New Era of Patient Prioritization - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
AI Triage vs. Emergency Room Triage: A New Era of Patient Prioritization The emergency department (ED) is the critical frontline of healthcare, where ra...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning